2011
DOI: 10.1021/la202561f
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Bisphosphonate Surface Functionalization and Acid Stability of Hierarchically Porous Titanium Zirconium Oxides

Abstract: To take advantage of the full potential of functionalized transition metal oxides, a well-understood nonsilane based grafting technique is required. The functionalization of mixed titanium zirconium oxides was studied in detail using a bisphosphonic acid, featuring two phosphonic acid groups with high surface affinity. The bisphosphonic acid employed was coupled to a UV active benzamide moiety in order to track the progress of the surface functionalization in situ. Using different material compositions, alteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…42,43 Furthermore, the relatively low surface area and high background activities of gold for many catalytic processes make the analysis of catalytically active adsorbates very difficult. 44 To address these issues and to compliment the array of available analytical techniques to study the surface- To transfer the HGC chemistry from the gold to the MO substrates, two strategies were employed: direct introduction of multiple suitable binding groups, geminal bisphosphonates (BP), 46 to the host scaffold (host 5, see Figure 1) or pre-functionalization of the MO substrates with propiolic acid and subsequent thiol-yne click chemistry on the surface. 47 Both strategies are schematically shown in Figure S15.…”
Section: Analysis Of Host-guest Complex Formation On Electrode Surfacesmentioning
confidence: 99%
“…42,43 Furthermore, the relatively low surface area and high background activities of gold for many catalytic processes make the analysis of catalytically active adsorbates very difficult. 44 To address these issues and to compliment the array of available analytical techniques to study the surface- To transfer the HGC chemistry from the gold to the MO substrates, two strategies were employed: direct introduction of multiple suitable binding groups, geminal bisphosphonates (BP), 46 to the host scaffold (host 5, see Figure 1) or pre-functionalization of the MO substrates with propiolic acid and subsequent thiol-yne click chemistry on the surface. 47 Both strategies are schematically shown in Figure S15.…”
Section: Analysis Of Host-guest Complex Formation On Electrode Surfacesmentioning
confidence: 99%
“…Furthermore, by preparing mesoporous layers of the MOs, higher surface areas are easily accessible, allowing for the use of further spectroscopic methods and simplifying the analysis of electrochemical data. To transfer the HGC chemistry from the gold to the MO substrates, two strategies were employed: direct introduction of multiple suitable binding groups, geminal bisphosphonates (BP), 44 to the host scaffold (host 5)…”
Section: Analysis Of Host-guest Complex Formation On Electrode Surfacesmentioning
confidence: 99%
“…We have shown that such materials display enhanced mass transport properties while at the same time retaining the high surface areas and uniform pores in the micro- and mesoporous range [32,33]. Both crystallization and surface capping with bisphosphonates produce highly acid-resistant materials [34]. We have also shown that pores at the higher end of the mesopore regime give enhanced diffusion kinetics [33,35].…”
Section: Introductionmentioning
confidence: 99%